Analysis of The Effect of Rewards, Organizational Structure, and Job Design on Employee Performance of Pt Pelabuhan Indonesia (Persero) Regional I - Yunita Sari Lingga; Soulthan Saladin Batubara (Journal of Research in Social Science and Humanities, 2025)
This research was conducted at PT Pelabuhan Indonesia (Persero) Regional I. The purpose of this research was to determine and analyze the influence of rewards, organizational structure, and product design on employee performance at PT Pelabuhan Indonesia (Persero) Regional I. The subjects of this study were 52 employees of PT Pelabuhan Indonesia (Persero) Regional I. The sample was drawn using the Slovin formula and random sampling technique. The method used was quantitative with an associative type. Data collection was carried out using a questionnaire and a Likert scale for variable measurement. The data analysis tool for this research was multiple linear regression using Statistical Package for the Social Sciences (SPSS) 24.0 software. The results showed that rewards had a positive and significant effect on employee performance, organizational structure had a positive and significant effect on employee performance, and job design had a positive and significant effect on employee performance. The results of this study found that rewards, organizational structure, and job design simultaneously had a positive and significant effect on employee performance at PT Pelabuhan Indonesia (Persero) Regional I.